Unearthing colonial complicities in Maasai collections at the Pitt Rivers Museum, Oxford - Van Broekhoven, L (Routledge, 2024)
The Pitt Rivers Museum (PRM) is the University of Oxford’s Museum of Anthropology and World Archaeology. Founded in 1884 when General Augustus Lane Fox Pitt Rivers donated his collection to the University, it is now a popular destination with over 500,000 visitors a year, 55,000 objects on display, and stewarding nearly 600,000 objects. It is widely regarded as one of the best museums of its kind while at the same time remains a contested space that calls for innovative curation to engage with the more difficult aspects of its history. In this chapter, I discuss The Maasai Living Cultures Project, initiated at the PRM in 2017. I consider how project outcomes were unforeseeable from the outset and developed pragmatically through conversation over an extended period, allowing partners to get to know each other and the matters at hand in detail. Our aim has been to develop open-ended, honest, mutually beneficial, and iterative approaches that include the physical return of objects but do not see that return as an oppositional choice between keeping and losing/community and museum, nor one that speaks of loss where objects are returned. The iterative, dialectical process has proven to be a defining, central outcome of the Maasai project. This process has kept minds open to different approaches and has welcomed uncharted pathways that could be ventured into safely with room for growth, trial, and error. The chapter outlines the possibilities and impossibilities of navigating these processes as part of our practice.